Effect of Ultrasound and Enzymes on the Extraction of Gallic Acid from Labisia Pumila (Kacip Fatimah) - Noor Adilah, Md Salehan; Ahmad Ziad, Sulaiman; Azilah, Ajit (2014)
Ultrasound and enzymes is unified to extract gallic acid from Labisa pumila (Kacip Fatimah). Gallic acid has anti-fungal and anti-viral properties and acts as an antioxidant which helps to protect cells against oxidative damage. Gallic acid was found to show cytotoxicity against cancer cells, without harming healthy cells. Besides the effect of ultrasound and the activity of Trichorderma reesei cellulase on the extraction productivity, solid-liquid mass transfer limitations will be investigated. The effects of extraction time, extraction temperature, solvent-to-solid ratio, and sonication power on the extraction of gallic acid were parameters considered into account for the research.